Urban expansion and compensation vis-a-vis livelihood coping strategies of displaced farmers surrounding medium size towns in north west Ethiopia - Meznanat Tame; Kassahun Gashu; Bantayehu Ayalew Workineh (City, Territory and Architecture)
Abstract Urban expansion and peri-urban agricultural land are counter competing each other. In developing countries rapid urban expansion are predominantly expected at the cost of croplands. The main objective of this study was to analyze urban expansion driving factors and compensation vis-a-vis livelihood coping strategies of displaced farmers surrounding medium size towns. Primary data were collected through 350 survey questionnaires, two FGDs and six key informant interviews. The result depicts that compensation strategy is mostly in terms of cash (money).The social relationship and value within the community before displacement revealed that most of the respondents (94%) was either very high or high compared to after displacement (67%). Binary logistic regression result showed the perception of displaced farmers’ towards urban expansion was significantly (P < 0.05) affected by gender, age, farm size, family size, education level and year of farming experience.The result implies that there is a need to curtail proper good urban land governance with participatory approach which includes farmers. The study finding also emphasized the need to implement appropriate urban planning, land and housing policy which should improve urban land use efficiency. Improving efficient use of urban land is imperative to protect farmland and ecosystems, mainly to tackle alarming urban expansion.